The Fiction of the Poet : In the Post-Symbolist Mode - Balakian, Anna, 1915-1997 (Book collections on Project MUSE., 1992)
Addressing all readers who value the beauty of language, Anna Balakian examines the work of five twentieth-century poets--Yeats, Valry, Rilke, Stevens, and Guilln--to show how the linguistic richness of the symbolist tradition continued well into the modern period. These writers, all of whom learned the poetry of language from Mallarm, compensated for the disappearance of metaphysical inclinations in early twentieth-century poetry by instituting a poetic fiction. Balakian finds the immersion of the ""I"" and its altered reflection in the work of art to be a common feature of their poetry, a